Modeling Air Temperature Inside an Organic Vegetable Greenhouse - Vita Ayu Kusuma Dewi; Budi Indra Setiawan; Budiman Minasny; Liyantono Liyantono; Roh Santoso Budi Waspodo (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2020)
Air temperature is an important microclimate parameter in a greenhouse as it influences root growth and controls plant growth and development. Thus, the precise monitor and model temperature under greenhouse is needed to maintain the plants in optimal conditions. This research aims to model the temperature under a greenhouse using energy balance model. The study monitored the temperature inside and outside the greenhouse in a humid tropical environment. Based on the data, heat exchange constants of greenhouse components were derived, they were: 0.0029 (solar radiation), 0.8 (air) and 0.01 (heat exchange from greenhouse component). The calibrated model enables the calculation of temperature inside a greenhouse based on its outside air temperature, wind speed, and solar radiation. Testing the model against an independent time series showed the high accuracy of the model with an R2 value of 0.99, RMSE = 0.0085 and model efficiency Ef = 0.99. Based on the results, most advantageous strategies for air temperature control inside the greenhouse include the control of air ventilation.